Assessing human resources for health: what can be learned from labour force surveys? - Dal Poz Mario R; Zurn Pascal; Diallo Khassoum; Gupta Neeru (BMC, 2003)
Abstract Background Human resources are an essential element of a health system's inputs, and yet there is a huge disparity among countries in how human resource policies and strategies are developed and implemented. The analysis of the impacts of services on population health and well-being attracts more interest than analysis of the situation of the workforce in this area. This article presents an international comparison of the health workforce in terms of skill mix, sociodemographics and other labour force characteristics, in order to establish an evidence base for monitoring and evaluation of human resources for health. Methods Profiles of the health workforce are drawn for 18 countries with developed market and transitional economies, using data from labour force and income surveys compiled by the Luxembourg Income Study between 1989 and 1997. Further descriptive analyses of the health workforce are conducted for selected countries for which more detailed occupational information was available. Results Considerable cross-national variations were observed in terms of the share of the health workforce in the total labour market, with little discernible pattern by geographical region or type of economy. Increases in the share were found among most countries for which time-trend data were available. Large gender imbalances were often seen in terms of occupational distribution and earnings. In some cases, health professionals, especially physicians, were overrepresented among the foreign-born compared to the total labour force. Conclusions While differences across countries in the profile of the health workforce can be linked to the history and role of the health sector, at the same time some common patterns emerge, notably a growing trend of health occupations in the labour market. The evidence also suggests that gender inequity in the workforce remains an important shortcoming of many health systems. Certain unexpected patterns of occupational distribution and educational attainment were found that may be attributable to differences in health care delivery and education systems; however, definitional inconsistencies in the classification of health occupations across surveys were also apparent.